Effect of occurrence of vitiligo in children over quality of life of their families: A hospital-based study using family dermatology life quality index - Pratik Gahalaut; Sandhya Chauhan; Amit Shekhar; Madhur Kant Rastogi; Nitin Mishra (Wolters Kluwer Medknow Publications, 2018)
Introduction: Vitiligo in an adult patient has a profound effect on the quality of life (QoL) of that particular patient. Although it is known that vitiligo in adult patient affects QoL in their family, very little information is available regarding QoL in a family having children suffering from vitiligo. Materials and Methods: This is a cross-sectional, hospital-based study to ascertain the effect children suffering from vitiligo have on the QoL of their respective families. Study participants were fifty healthy parent/immediate caregivers of fifty corresponding children suffering from vitiligo. The QoL in the family of these vitiliginous children was assessed with the help of Family Dermatology Life Quality Index (FDLQI). Results: There was significantly more impairment of FDLQI among respondents if vitiliginous child was female compared to male. The total FDLQI showed a significant negative correlation with duration of vitiligo in children. Analysis of individual items in FDLQI revealed emotional distress as the most impaired facet of FDLQI and housework as the least affected item. Conclusion: Presence of vitiligo in children affects the QoL of that particular child and his/her family. This impairment of FDLQI is more if the child suffering from vitiligo is female. Treatment of vitiligo in pediatric age group should include psychological counseling and support for the child as well as their parents/caregivers.